2002
DOI: 10.3727/036012902816026077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin and Electroacupuncture (Ea) on Nk Cell Activity, Interleuk1n-2 Production and Pomc-Derived Peptides in Traumatic Rats

Abstract: The present study was to evaluate the effect of melatonin (MT) and EA on the cytotoxic activity of natural killer (NK) cells, the dynamic changes of the induction of interleukin-2(IL-2) and the content of POMC-derived peptides, beta-endorphins (betaE) and ACTH in spleen lymphocytes and in plasma of traumatic rats. The results showed that intraperitioneal (i.p.) injection of MT was able to recover the lower levels of NK cell activity and the induction of IL-2 production; MT could also decrease the higher betaE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…To make matters more confusing, exogenous melatonin administration allegedly enhanced the ADCC in mice , while in another study, melatonin enhanced ADCC in summer, but not in winter . More recently, it was found that intraperitoneal injection of melatonin recovered the reduced NK cell activity of traumatized rats . Finally, exogenous melatonin increased the NK cell activity in aged mice and recovered the diminished NK cell activity induced by the immunotoxicity of cadmium and lead in mice.…”
Section: Natural Killer Cellsmentioning
confidence: 96%
“…To make matters more confusing, exogenous melatonin administration allegedly enhanced the ADCC in mice , while in another study, melatonin enhanced ADCC in summer, but not in winter . More recently, it was found that intraperitoneal injection of melatonin recovered the reduced NK cell activity of traumatized rats . Finally, exogenous melatonin increased the NK cell activity in aged mice and recovered the diminished NK cell activity induced by the immunotoxicity of cadmium and lead in mice.…”
Section: Natural Killer Cellsmentioning
confidence: 96%
“…At supra-physiological concentrations, melatonin induces T-cell proliferation and upregulation of pro-inflammatory cytokines [43,57] . Exogenous melatonin administration increases the proliferative response of rat lymphocytes [58] , increases the number of NK cells [59,60], stimulates the pro-inflammatory cytokines IL-1 and TNF- [61,62] and enhances phagocytosis [63]. Melatonin exerts a concentration-dependent effect on the immune system.…”
Section: Effect Of Exogenous Melatonin On Inflammatory Parametersmentioning
confidence: 99%
“…Histological methods allow to establish the time of both one-stage and two-stage liver ruptures, in particular, the term of hematoma formation under its body capsule or in the depths of its parenchyma with a rupture or without apparent rupture of parenchyma, which begin to appear at the moment of capsule rupture in the place of the hematoma, and gradually accumulate in remote periods after an injury, which leads to diagnostic errors in medical practice. These methods are also helpful in determining the absence effect of alcohol intoxication [4][5][6][7][8][9][10][11][12][13][14][15][16] . It is necessary to differentiate the characteristic morphological picture which is revealed by the histological study of liver catarrhal hematomas (from the region of subcapsular lesions, from the places of hematomas and the capsule rupture in accordance with the location of the subcapsular hematoma, intact parts of the liver outside its primary and repeated rupture) 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Information on the frequency of liver damage in case of mechanical injury is controversial in literature sources. Some authors, when studying the features of blunt trauma, found out that the frequency of liver damage was 58.7% among other injuries of internal organs [11][12][13] . At the same time, it was noted that the right liver was damaged in 62.2% of the cases and its left lobe was injured in 10.7% of cases, both parts were simultaneously damaged in 15.5% of cases [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%